Traditional Chinese Mind and Body Exercises for Neck Pain: A Meta-Analysis of Randomized Controlled Trials. (1st October 2021) - Xie, Yu-Hua; Liao, Man-Xia; Wang, Mao-Yuan; Fernando, W. C. Hewith A.; Gu, Yue-Ming; Wang, Xue-Qiang; Liao, Lin-Rong
Abstract : Background . Neck pain is common and can have a significant impact on patients' physical functionality, mobility, and quality of life (QOL). In clinical practice, traditional Chinese mind and body exercise (TCMBE) is a combination of different types of exercise based on traditional Chinese medicine, including qigong, tai chi, the 12-words-for-life-nurturing exercise, and so on, and many studies have found that it is safe and effective at helping patients with neck pain. Objective . The aim of this study was to investigate the effectiveness of TCMBE on pain intensity, functional mobility, and QOL in individuals with neck pain. Methods . The PubMed, MEDLINE, PEDro, and Embase databases were systematically searched for relevant studies. Randomized controlled trials reporting the effects of TCMBE on pain intensity, functional mobility, and QOL in individuals with neck pain were included. Screening, data extraction, and literature quality assessments were performed independently by two reviewers. RevMan5.4 software was used for data analysis. Results . Six studies with 716 participants met the inclusion criteria. Compared with the control groups, TCMBE had no therapeutic advantage in improving pain intensity (visual analogue scale: mean difference (MD) = 1.8, 95% confidence interval (CI): −7.70 to 11.46, and P = 0.70); functional mobility (neck disability index: MD = 0.15, 95% CI: −6.37 to 6.66, and P = 0.96; neck pain and disability scale: MD = 1.31, 95% CI: −4.10 to 6.71, and P = 0.64); or 36-item short-form health survey (SF-36) scores for physical function (MD = 5.58, 95% CI: −8.03 to 19.18, and P = 0.42), general health (MD = 1.87, 95% CI: −4.99 to 8.72, and P = 0.59), body pain (MD = 2.26, 95% CI: −3.80 to 8.32, and P = 0.46), vitality (MD = 6.24, 95% CI: −1.49 to 13.98, and P = 0.11), social function (MD = 8.06, 95% CI: −4.85 to 20.98, and P = 0.22), role physical (MD = –1.46, 95% CI: −8.54 to 5.62, and P = 0.69), or role emotional (MD = 6.5, 95% CI: −3.45 to 16.45, and P = 0.2). However, TCMBE was less effective at improving mental health results based on the SF-36 survey (MD = 3.37, 95% CI: 0.5 to 6.24, and P = 0.02). Conclusions . Based on the meta-analysis, there is insufficient evidence to support the clinical use of TCMBE in improving pain intensity and enhancing functional mobility and QOL in individuals with neck pain.